Neutrino masses and the scalar sector of a B-L extension of the standard model - Montero, J. C. [UNESP]; Sanchez-Vega, B. L. [UNESP] (Amer Physical Soc, 2011)
We consider an electroweak model based on the gauge symmetry SU(2)(L) circle times U(1)(Y') circle times U(1)(B-L) which has right-handed neutrinos with different exotic B - L quantum numbers. Because of this particular feature we are able to write Yukawa terms, and right-handed neutrino mass terms, with scalar fields that can develop vacuum expectation values belonging to different energy scales. We make a detailed study of the scalar and the Yukawa neutrino sectors to show that this model is compatible with the observed solar and atmospheric neutrino mass scales and the tribimaximal mixing matrix. We also show that there are dark matter candidates if a Z(2) symmetry is included.